Seismic hazard map of India and neighbouring regions. Issue 163 (December 2022) - Sreejaya, K.P.; Raghukanth, S.T.G.; Gupta, I.D.; Murty, C.V.R.; Srinagesh, D.
Abstract: This article presents probabilistic seismic hazard analysis (PSHA) of India and adjoined region, carried out to develop a new national seismic hazard map for India. The hazard map is developed using fault oriented spatially smoothed seismicity approach. A catalog of earthquakes has been compiled for the region (Latitude 5 0 N − 40 0 N and Longitude 65 0 E − 100 0 E) from 2600BCE to 2019CE to estimate the seismicity parameters. Eighteen suitable ground motion prediction equations in the logic tree framework are used for the four major geological regions of the country. The hazard is estimated at rock sites (B-C boundary type) conditions in terms of peak ground acceleration (PGA), short-period (0.2 s), and long-period (1s) spectral acceleration maps and uniform hazard spectra, with 2% and 10% probabilities of exceedance in 50 years. Higher hazard values are observed in the Hindukush-Pamir regions and Northeast India, whereas central India and the southern peninsular regions are less prone to seismic threat. The proposed maps find their application in the seismic design of structures, risk assessment, and as an input for updating the existing code provisions. Highlights: The study is carried out with the motivation to update the Indian seismic code zone map of IS 1893. A careful Investigation of several source models reveals that the fault-oriented spatially smoothed model is more effective for the analysis. A well-established ranking scheme is used to rank the candidate GMPEs and obtain the logic tree weights. A higher hazard is observed in the western Himalaya and Northeast India and lower hazard at Central and southern India.